3D PRINTING TECHNOLOGIES IN SABAH HANDICRAFT INDUSTRY: A PRELIMINARY INVESTIGATION: 3D PRINTING TECHNOLOGIES IN SABAH HANDICRAFT INDUSTRY: A PRELIMINARY INVESTIGATION - Lilian Lee Shiau Gee; Saila Saidie, (Jurnal Gendang Alam (GA), 2024)
ABSTRACT To enter emerging markets, it is necessary to revitalise and modernise handmade items, crafts, and souvenirs. The preservation of Borneo's artisan handicrafts and traditional techniques, which are directed by generational knowledge, necessitates the introduction of new offers to invigorate the growth of these traditional crafts that are at risk of fading. The progress of 3D printing enables the exploration of personalisation, uniqueness, and creativity, which may contribute to the diversification of Borneo handcrafted items. Hence, the integration of innovative technologies and materials may be enthusiastically adopted by local artisans and the expansion of technology as an independent domain capable of manufacturing a diverse array of craft products can enhance their production, competitiveness, and prospects for sustainability. The desire to include state-of-the-art technology in the construction of mementos raises several philosophical and ethical concerns that need to be addressed. The study suggests that further investigation should be conducted to explore the advantages and disadvantages of 3D printed mementos for various client categories. Incorporating the cultural heritage of the Borneo people into product design, together with the use of digital manufacturing technologies, may ultimately create fresh value, enhance resilience, and promote sustainability for local handcrafted items. Keywords: 3D Printing, Sabah Handicraft, Design Intervention, Local Artisan, consumer preferences.